A diminished sciatic nerve structural integrity is associated with distinct peripheral sensory phenotypes in individuals with type 2 diabetes - Mooshage, Christoph; Tsilingiris, Dimitrios; Schimpfle, Lukas; Seebauer, Lukas; Eldesouky, Omar; Aziz-Safaie, Taraneh; Hohmann, Anja; Herzig, Stephan; Szendrödi, Julia; Nawroth, Peter Paul; Heiland, Sabine; Bendszus, Martin; et al. (Diabetologia, 2023)
Quantitative sensory testing (QST) allows the identification of individuals with rapid progression of diabetic sensorimotor polyneuropathy (DSPN) based on certain sensory phenotypes. Hence, the aim of this study was to investigate the relationship of these phenotypes with the structural integrity of the sciatic nerve among individuals with type 2 diabetes.
Gesehen am 18.06.2024